Pharmacophore model for antiepileptic drugs acting on sodium channels - Tasso, Silvina Mabel (2001)
Fifteen antiepileptic drugs (AED), active against the maximal electroshock seizure test and able to block the neuronal voltage-dependent sodium channel, have been studied by means of a similarity analysis. Structural and electronic, quantum chemically derived characteristics are compared. Rigid analogs are included, because of the flexibility of some structures, in order to discern the conformational requirements associated with these ligands in the moment of the interaction. An inactive compound (ethosuximide) helps in the definition of the structural factors that are important for the activity. We propose a pharmacophore model that, giving an interpretation of the biological activity, allows the design of new AED with a well-defined mechanism of interaction.